Venous stroke–a stroke subtype that should not be ignored - Zhou, Yifan; Jiang, Huimin; Wei, Huimin; Liu, Lu; Zhou, Chen; Ji, Xunming (Frontiers in Neurology, 2022)
Based on the etiology, stroke can be classified into ischemic or hemorrhagic subtypes, which ranks second among the leading causes of death. Stroke is caused not only by arterial thrombosis but also by cerebral venous thrombosis. Arterial stroke is currently the main subtype of stroke, and research on this type has gradually improved. Venous thrombosis, the particular type, accounts for 0.5–1% of all strokes. Due to the lack of a full understanding of venous thrombosis, as well as its diverse clinical manifestations and neuroimaging features, there are often delays in admission for it, and it is easy to misdiagnose. The purpose of this study was to review the pathophysiology mechanisms and clinical features of arterial and venous thrombosis and to provide guidance for further research on the pathophysiological mechanism, clinical diagnosis, and treatment of venous thrombosis. This review summarizes the pathophysiological mechanisms, etiology, epidemiology, symptomatology, diagnosis, and treatment heterogeneity of venous thrombosis and compares it with arterial stroke. The aim is to provide a reference for a comprehensive understanding of venous thrombosis and a scientific understanding of various pathophysiological mechanisms and clinical features related to venous thrombosis, which will contribute to understanding the pathogenesis of intravenous stroke and provide insight into diagnosis, treatment, and prevention.